2019
DOI: 10.1002/anie.201911266
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Resonance Induced Thermally Activated Delayed Fluorophores for Narrowband Green OLEDs

Abstract: High-color-purity emissions with small af ull-width at half-maximum (FWHM) are an ongoing pursuit for highresolution displays.T hough the flourishment of narrow-band emissive materials with multi-resonance induced thermally activated delayed fluorescence (MR-TADF) in the blue region, such materials have not validated their potential in other color regions.Byamplifying the influence of skeleton and peripheral units,as eries of highly efficient green-emitting MR-TADF materials are firstly reported. Peripheral un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
322
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 468 publications
(354 citation statements)
references
References 40 publications
8
322
0
1
Order By: Relevance
“…It is worth noting that, though few TADF‐OLEDs with similar CIEs showed relatively higher EQE max , device D2 showed the state‐of‐the‐art performances with brightness >1000 cd m −2 , which is more adequate for practical applications, testifying the great potential of TSF‐OLEDs for narrow‐band emission. [ 26,6b ] Besides, arising from the adoption of TADF host in favor of low voltages, the highest PE max was observed for D2 among all devices summarized.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that, though few TADF‐OLEDs with similar CIEs showed relatively higher EQE max , device D2 showed the state‐of‐the‐art performances with brightness >1000 cd m −2 , which is more adequate for practical applications, testifying the great potential of TSF‐OLEDs for narrow‐band emission. [ 26,6b ] Besides, arising from the adoption of TADF host in favor of low voltages, the highest PE max was observed for D2 among all devices summarized.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, there exists only a single report of green MR-TADF OLEDs with l EL ranging from 493-501 nm and EQE max ranging from 21-22%. 22 The results demonstrate how to design MR-TADF emitters exhibiting both a red-shifting of the emission and a suppression of concentration quenching in the solid state.…”
Section: Introductionmentioning
confidence: 87%
“…Importantly, the EQE maintains a high value of 20.1% at practical high luminance of 1000 cd m −2 . Compared with a very recently reported high‐performance narrowband green OLED based on a MR‐TADF material (FWHM: 39 nm; CIE: (0.20, 0.58); EQE: 21.0% at 1000 cd m −2 ), [ 12 ] our device with 2 wt% doping concentration features a narrower EL band and a better color purity while maintaining a very close EQE at practical high luminance, although the efficiency of the device is still not comparable to those of some ultraefficient green devices with EQE max over 30%. [ 32b,33 ] To improve the purity for green emission and EQE, the molecular structure modification and device configuration optimization will be performed in the future.…”
Section: Figurementioning
confidence: 95%
“…Very recently, Zhang et al reported several green MR‐TADF compounds, which exhibit narrowband EL (FWHM: 32–40 nm) with high EQE max (20.9–22.7%), but the best CIE coordinates of (0.20, 0.58) largely deviated from the NTSC standard (CIE: (0.21, 0.71)). [ 12 ] So far, the development of efficient narrowband green emitters that can achieve pure green EL with the CIE coordinates that approach the mainstream NTSC standard remains an unaddressed issue.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation